2022
DOI: 10.37394/23207.2023.20.8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Innovation Potential of Personnel on Strengthening Economic Security of Ukrainian Enterprises in the Post-War Period

Abstract: The article aims to determine the influence of the innovation potential of personnel on strengthening economic security of Ukrainian enterprises in the post-war period. The object of the article is the process of strengthening economic security of Ukrainian enterprises considering the use of innovation potential of their personnel. The study uses general scientific theoretical methods: generalization, explanation, grouping - to analyze economists’ views of the study object and draw conclusions of the content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Also, we support scientists (Babenko V. et al, 2017) who proposed a model of adaptive management, in the framework of which it is proposed to use a deterministic approach for modeling taking risks into account. We share the opinion of the authors of the article (Cherep A. et al, 2023) regarding the relevance of research on the impact of the innovative potential of personnel on strengthening the economic security of enterprises in the post-war period. Also, in our opinion, the study (Y.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, we support scientists (Babenko V. et al, 2017) who proposed a model of adaptive management, in the framework of which it is proposed to use a deterministic approach for modeling taking risks into account. We share the opinion of the authors of the article (Cherep A. et al, 2023) regarding the relevance of research on the impact of the innovative potential of personnel on strengthening the economic security of enterprises in the post-war period. Also, in our opinion, the study (Y.…”
Section: Discussionmentioning
confidence: 99%
“…Scientists (Cherep A. et al, 2023) investigated the impact of the innovative potential of personnel on strengthening the economic security of Ukrainian enterprises in the postwar period. The authors identified four obstacles to the positive impact of the innovative The article (Samoilenko Yu.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Важливим є дослідження групи авторів A. Cherep, M. Adamenko, O. Cherep & I. Dashko [2], які дослідили вплив інноваційного потенціалу персоналу на стан економічної безпеки підприємств, напрями формування інноваційного потенціалу працівників.…”
Section: огляд літературиunclassified
“…The content of personnel policy is work with personnel in accordance with the concept of enterprise development as the basis of effective enterprise activity. The purpose of the personnel policy is to ensure an optimal balance of the processes of updating and preserving the quantitative and qualitative composition of personnel in its development in accordance with the needs of the organization itself, therefore this policy must meet the requirements of the current labor legislation and the state of the labor market in the region [11].…”
Section: Presentation Of the Main Research Materialsmentioning
confidence: 99%